Systematic Literature Review (SLR): Program Makan Bergizi Gratis Dalam Perspektif Maqashid Syariah - Indah Nuraini; Mawardi; Heri Sutopo; Ulil Albab (DPPM Universitas Pelita Bangsa, 2025)
Malnutrition and food insecurity remain significant challenges, especially in Muslim-majority countries. Free nutritious meal programs have emerged as strategic efforts to improve public health, particularly among vulnerable groups such as schoolchildren and pregnant women. This study employs a Systematic Literature Review (SLR) approach to examine the alignment of these programs with the principles of Maqashid Syariah, which emphasize the protection of life, intellect, and progeny. The findings reveal that such programs positively impact nutritional security, educational outcomes, and social development. When implemented based on Islamic values—such as ensuring halal-thayyib food standards and involving community-based initiatives through zakat and waqf—their sustainability and effectiveness are significantly enhanced. In conclusion, integrating Maqashid Syariah into free meal programs not only strengthens health and education outcomes but also serves as a comprehensive strategy for sustainable development aligned with Islamic ethical values.